Self-assessment in head and neck surgery and oncology - O'Neill, James Paul; Shah, Jatin P. (Elsevier Saunders, 2015)
Self-Assessment in Head and Neck Surgery and Oncology is a one-of-a-kind, comprehensive medical reference book that showcases international, expert knowledge and judgment in the practice of head and neck surgery and oncology. It offers a variety of true/false statements and multiple-choice questions, as well as patient and case histories, coverage of the newest technologies, and much more. This brand-new resource is perfectly suited for otolaryngology residents, oncologists, and surgeons who wish to measure their understanding of how to effectively manage the day-to-day problems and issues arising in patients with neoplasms of the head and neck.